Compreensão de diferenças culturais para identificar pessoas com potenciais interesses comuns em sites de redes sociais - Astolfi, Gilberto (Universidade Federal de São Carlos, 2010)
In this research we described a way to obtain a method, through a cyclical approach of work, which goals to identify people, users of social networks that are talking about the same subject. The motivation for obtaining this method came from the perceived problem in the Social Network Management Systems, which is to identify and/or group people around the same issue in order to make social touch possible among them. The differential this method is related to consider people's culture as the main point to try to identify the various forms they have to express themselves on a particular issue, and thereby to observe what people are writing about it in the social networks, considering the many ways in which people express themselves. In this context, this method makes use of cultural information get by the Open Mind Common Sense in Brazil Project (OMCS-Br), that goal to collect Brazilians‟ cultural knowledge (ANACLETO, 2008), in order to identify similarity of contexts among different vocabularies. With the purpose of to observe the feasibility of this method, we performed a case study with the participation of people that through questionnaires could opine on the results obtained by the method, in order to observe the feasibility of its applicability.
Keywords: Ciência da computação; Senso comum; Análise semântica; Cultura; Cultura popular; Common sense; Social networking; Semantic textual comparisons; Context; Culture; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO